2018
DOI: 10.2989/16085906.2017.1394332
|View full text |Cite
|
Sign up to set email alerts
|

The role of children in their HIV-positive parents’ management of antiretroviral therapy in Uganda

Abstract: Adjustment to life on antiretroviral therapy (ART) and living with HIV as a long-term chronic condition, pose significant medical, social and economic challenges. We investigated children's role in supporting HIV-positive parents to self-manage life on ART. Between 2010 and 2012, we conducted a qualitative study using semi-structured interviews with 38 HIV-positive parents who had been on ART for over a year. They were randomly selected from people accessing ART from three delivery sites in Wakiso district, Ug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…New studies also confirmed this theme with more detailed examples of various forms of support that can help PLHIV cope with lifelong ART [ 14 , 16 20 , 26 , 35 , 36 , 43 , 45 , 47 , 49 , 56 , 57 , 61 , 66 68 , 76 , 81 , 82 , 84 , 89 91 ]. Health services can be more supportive by offering adolescent-friendly clinics, mobile services, increased ART days, free services, and improved access to care.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…New studies also confirmed this theme with more detailed examples of various forms of support that can help PLHIV cope with lifelong ART [ 14 , 16 20 , 26 , 35 , 36 , 43 , 45 , 47 , 49 , 56 , 57 , 61 , 66 68 , 76 , 81 , 82 , 84 , 89 91 ]. Health services can be more supportive by offering adolescent-friendly clinics, mobile services, increased ART days, free services, and improved access to care.…”
Section: Resultsmentioning
confidence: 77%
“…Our understanding of adolescents’ experiences with HIV and ART was enriched considerably [ 11 , 12 , 26 , 38 , 41 , 54 , 56 , 63 , 69 , 87 ]. Generally, adolescents living with HIV do not receive the support they need to understand their illness and the impact of HIV on their future, engage in care and adhere to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Kenya National Bureau of Statistics (KNBS, 2018) indicates that seven million Kenyans are unemployed, a situation which hampers financial support to elderly parents by adult children, available literature indicate that apart from financial assistance, adult children provide other forms of support. This is evident from research by Nalugya et al (2018) in Namibia, South Africa, Tanzania Vol 8 Issue 7 DOI No. : 10.24940/theijhss/2020/v8/i7/HS2007-069 July , 2020…”
Section: Literature Reviewmentioning
confidence: 95%
“…Some unemployed adult children with no monetary support kept their parents' company. It is emphasized by Nalugya et al, (2018) that most young people comfort their parents, giving them hope and reassurance, offering advice, being confidants and just being there for them. Adult children also support parents by renovating their old houses or building them new ones to ensure decent shelter.…”
Section: Children's Support For Parentsmentioning
confidence: 99%
“…Although health professionals such as nurses may understand HIV/AIDS, the causes and mode of transmission, they continue to harbour negative attitudes towards supporting PLWH because of a fear of contracting the disease 18 . The barriers and negative attitudes towards PLWH found in Ghana are comparable to those reported in studies conducted in other African countries such as Kenya, 19,20 Tanzania 21 and Uganda 22–25 . These trends underscore the need to adopt strategies to change attitudes and enhance the well‐being of PLWH.…”
Section: Introductionmentioning
confidence: 90%